SUCCESS IN ADVANCE CARE PLANNING: THE CHANGING GOAL POST?. Issue 2 (1st June 2013) - Knight, K
Abstract : Background: Since its inception advance care planning (ACP) has generated passionate advocates and severe critics. In 2004 a Hastings Center Report publication claimed that the living will has failed, yet we gather at the 4th international conference of ACP suggesting that the idea is thriving. How can such adverse positions coexist? Aim: This paper aims to clarify ideas of success in ACP in order to make sense of the disagreements. Method: Literature review and critical reflection Results: ACP is promoted in pursuit of a combination of utilitarian, libertarian and/or compassionate aims and notions of ACP success vary considerably. In the empirical literature success either refers to successful programme implementation, the achievement of an ideological good for a patient or both. A historical evolution of types of success criteria is evident and ambitions as to what constitute adequate markers of success are diverse. Discussion: As a complex multidisciplinary field ACP provides a fertile ground for partial successes and failures. A particular problem is that addressing shortcomings in one area can often only be achieved by reducing ambitions in others, leading to a dynamic shifting of ACP goals. Criticisms from one discipline are evaded through discipline specific research design or via different discipline specific goals and ambitions. Conclusion: Whether ACP is seen as successful depends on how many and which goals ACP is meant to address at once. Although modern ACP has made many practical advances, it has done so at significant cost elsewhere and certain criticisms remain relevant.